2012
DOI: 10.1111/j.1528-1167.2012.03566.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress sensitivity of childhood epilepsy is related to experienced negative life events

Abstract: SUMMARYPurpose: To evaluate the effect of stress on seizure frequency in childhood epilepsy, and to assess possible differences between children in whom seizures are precipitated by stress and those in whom they are not. Methods: Parents or caregivers of children with active epilepsy (aged 2-16 years) were sent questionnaires on developmental and epilepsy characteristics, life-time stress exposure, and the effect of stressful periods and moments of acute stress on seizure frequency in their child. Further info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 54 publications
1
29
1
Order By: Relevance
“…32 An association between early life stress and stress sensitivity of seizures has been shown previously. 33 Most studies comparing people with epilepsy in the interictal state with healthy controls reported higher functional connectivity in epilepsy. 19,20,34,35 An increase in theta band functional connectivity was associated with seizure frequency in tumor-related epilepsy.…”
Section: Cortisol and Functional Connectivitymentioning
confidence: 99%
“…32 An association between early life stress and stress sensitivity of seizures has been shown previously. 33 Most studies comparing people with epilepsy in the interictal state with healthy controls reported higher functional connectivity in epilepsy. 19,20,34,35 An increase in theta band functional connectivity was associated with seizure frequency in tumor-related epilepsy.…”
Section: Cortisol and Functional Connectivitymentioning
confidence: 99%
“…The seizure precipitant most often reported is stress [1][2][3][4][5][6][7]. The relation between stress and seizures is expected to be mediated by stress hormones like corticotrophinreleasing hormone (CRH), adrenocorticotropic hormone (ACTH), and cortisol, affecting neuronal excitability and seizure threshold [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…To detect Dravet-specific reported seizure precipitants, we compared these in the cohort with Dravet syndrome with precipitants reported in two cohorts recently studied: a cohort with childhood epilepsy from the same University Medical Centre and a communitybased cohort with epilepsy from the same geographical region [13,14].…”
Section: Cohort With Childhood Epilepsy and Community-based Cohort Wimentioning
confidence: 99%
“…Of the 345 patients fulfilling the selection criteria, 153 (44%) had responded. The purpose of this questionnaire-based study was to address the relationship between stress, among other seizure precipitants, and epilepsy [13].…”
Section: Cohort With Childhood Epilepsy and Community-based Cohort Wimentioning
confidence: 99%
See 1 more Smart Citation